Persepsi Keadilan, Sistem Perpajakan dan Diskriminasi Terhadap Etika Penggelapan Pajak - Sekar Akrom Faradiza (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
The many cases of tax evasion in Indonesia have caused huge losses to the country. This causes tax evasion to be ethical or fair to do considering the many actions that should not be carried out by the tax apparatus. This study aims to examine whether the perception of justice, the taxation system and perceived discrimination by taxpayers can affect the perception of taxpayers on the tax evasion ethics. The data used in this study was obtained using a survey conducted to taxpayers registered in the tax service office in Yogyakarta and Central Java. Data analysis was performed using multiple linear regression analysis. The results of the study show that justice, taxation systems and discrimination affect the ethical perception of tax evasion.